GenBank. Issue Volume 47:Issue D1(2019) (26th October 2018) - Sayers, Eric W; Cavanaugh, Mark; Clark, Karen; Ostell, James; Pruitt, Kim D; Karsch-Mizrachi, Ilene
Abstract: GenBank® (www.ncbi.nlm.nih.gov/genbank/ ) is a comprehensive database that contains publicly available nucleotide sequences for 420 000 formally described species. Most GenBank submissions are made using BankIt, the NCBI Submission Portal, or the tool tbl2asn, and are obtained from individual laboratories and batch submissions from large-scale sequencing projects, including whole genome shotgun (WGS) and environmental sampling projects. Daily data exchange with the European Nucleotide Archive (ENA) and the DNA Data Bank of Japan (DDBJ) ensures worldwide coverage. GenBank is accessible through the NCBI Nucleotide database, which links to related information such as taxonomy, genomes, protein sequences and structures, and biomedical journal literature in PubMed. BLAST provides sequence similarity searches of GenBank and other sequence databases. Complete bimonthly releases and daily updates of the GenBank database are available by FTP. Recent updates include an expansion of sequence identifier formats to accommodate expected database growth, submission wizards for ribosomal RNA, and the transfer of Expressed Sequence Tag (EST) and Genome Survey Sequence (GSS) data into the Nucleotide database.